Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jrfm13110264
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Trends in Sustainable Corporate Finance: A Bibliometric Systematic Review

Abstract: Sustainable corporate finance is an attractive field of study in sustainability literature; however, the literature lacks systematic bibliometric analysis that provides a comprehensive review to clarify state-of-the-art sustainable corporate finance and that discusses new opportunities and potential instructions for further studies. To address this gap, this study adopts a literature review, bibliometric analysis, network analysis and co-wording technique to systematically investigate the Scopus database. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 175 publications
1
35
0
Order By: Relevance
“…Our results also indicated that US is the most productive country in the domain of financial risk and similar results are obtained by Chun-Hao et al (2012). A similar kind of result is also obtained by Bui et al (2020) while conducting bibliometric analysis for sustainable finance. Journal of banking and finance is having the highest h-index and g-index as per our results and similar result were obtained by Chun-Hao et al (2012).…”
Section: Final Discussion and Conclusionsupporting
confidence: 87%
“…Our results also indicated that US is the most productive country in the domain of financial risk and similar results are obtained by Chun-Hao et al (2012). A similar kind of result is also obtained by Bui et al (2020) while conducting bibliometric analysis for sustainable finance. Journal of banking and finance is having the highest h-index and g-index as per our results and similar result were obtained by Chun-Hao et al (2012).…”
Section: Final Discussion and Conclusionsupporting
confidence: 87%
“…The bibliometric analysis is approached to identify the SSCF indicators based on the data of all publications in the Scopus database using VOSviewer software to provide visuality results (Shukla et al , 2019). The FDM is applied to eliminate those invalid SSCF indicators by computing the experts' linguistic references (Bui et al , 2020a, b). The EWM converts the indicators' occurrence value into comparable weights to determine the regional performances (Tseng, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For future research, we suggest using the approach of Peters and Waterman, who, back in 1982, established the basic criteria for corporate excellence several of which are concerned business ethics, with the possibility of enlarging their outcomes of the importance and the advantages brought by corporate social responsibility and intellectual capital when it comes to enhancing profit, productivity, and performance (Popescu and Popescu 2019). Very essential also would be to incorporate outcomes of Bui et al (2020) to research aimed at business ethics. The author identified the knowledge gaps of sustainable corporate finance ((1) corporate finance in sustainability; (2) sustainable competitive advantages; (3) sustainable stakeholder engagement; (4) circular economy; (5) sustainable corporate finance innovation and risk management; and (6) sustainable supply chain ethics)).…”
Section: Discussionmentioning
confidence: 99%